Domestic Roles, Gender Responsibility, and Justice in Islamic Law: The Position of Wives as Housewives - Suprihatin (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2026)
This article recontextualizes the societal understanding of the role of wives as housewives within the framework of Islamic law, challenging perceptions that associate this role with oppression or injustice. The study employs a normative legal research method, using statutory analysis, Islamic legal sources (the Qur’an, Hadith, and fiqh doctrines), and conceptual–doctrinal interpretation to examine the legal construction of domestic roles. The findings demonstrate that the designation of a wife as a housewife is consistent with Islamic legal principles. However, the study identifies a critical tension arising from rigid, gender-based divisions of labor that dichotomize domestic and public spheres, often positioning domestic responsibilities exclusively upon wives while assigning public authority to husbands. The analysis shows that Islamic law conceptualizes the domestic sphere as a shared domain of responsibility between spouses, grounded in mutual leadership (jamā‘iyyah al-qiyādah al-ri‘āyah), cooperation, and accountability, while also permitting wives’ participation in public life under theonomic ethic and familial considerations. This article contributes to Islamic legal scholarship by offering a contextual reinterpretation of domestic norms that reconciles statutory family law with Islamic jurisprudence, promoting a justice-oriented, cooperative, and non-hierarchical model of family life.